2015
DOI: 10.4184/asj.2015.9.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss in Surgery for Aggressive Vertebral Haemangioma with and without Embolisation

Abstract: Despite their benign nature some symptomatic aggressive vertebral haemangiomas (AVH) require surgery to decompress spinal cord and/or stabilise pathological fractures. Preoperative embolisation may reduce the considerable blood loss during surgical decompression. This systematic review investigated whether preoperative embolisation reduced surgical blood loss during treatment of symptomatic AVH. PubMed Medline, Web of Science, and Ovid Medline were searched for case reports and clinical studies on surgical AVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…This study found that in the group that received preoperative embolization, blood loss was significantly less than in the group that did not (980 vs 1629 ml, respectively). 60 Cotten et al 15 reported that preoperative embolization can be used in combination with vertebroplasty to even further reduce blood loss during surgery.…”
Section: Endovascular Embolizationmentioning
confidence: 99%
“…This study found that in the group that received preoperative embolization, blood loss was significantly less than in the group that did not (980 vs 1629 ml, respectively). 60 Cotten et al 15 reported that preoperative embolization can be used in combination with vertebroplasty to even further reduce blood loss during surgery.…”
Section: Endovascular Embolizationmentioning
confidence: 99%
“…In accordance with the principles of biomechanics concerning vertebral fractures [23] , [24] , this clinical case did not require any posterior stabilization system with screws and rods, because the articular processes were spared. Pre-operative embolization may provide reduction of bleeding risks in selected cases [25] , [26] , but in our case embolization was not performed because the specific clinical picture urged rapid treatment and the our surgical approach (laminectomy with lesion removal) exposed to a lower risk of bleeding compared to anterior corpectomy. After the partial lesion removal, radiation therapy was recommended for this patient, because it has been demonstrated to be able to reduce local recurrence, but the patient did not undergo the procedure.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we performed preoperative embolization for all patients undergoing S3 hemangioma surgery to reduce intraoperative blood loss. Robinson et al [22] compared the intraoperative blood loss of patients who underwent preoperative embolization with that of those who did not undergo preoperative embolization and found that preoperative embolization significantly reduced intraoperative blood loss. Other additional factors, including anesthesia, surgical skill, and patient coagulation, might also cause intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%